GENTAMICIN PHARMACOKINETIC VARIABILITY IS INFLUENCED BY CHOICE OF ADMINISTRATION ROUTE. Issue 1 (14th December 2015) - Lala, Anita; Medlicot, Natalie; Broadbent, Roland; McCaffrey, Frances; Reith, David
Abstract : Introduction: A critically ill neonate may have several routes of venous access available, operating at different flow rates and with different dead-volumes, and therefore with different delivery kinetics. Aims: To determine which lumen of a double lumen umbilical venous catheter (UVC) would be used for administration of intravenous gentamicin to a premature baby and what flush volume would be used. Methods: An individual self-administered questionnaire was completed by Dunedin Hospital NICU nurses in April-May 2014. The questionnaire consisted of two scenarios describing babies of 24 and 32 weeks gestation, and asked that the site of administration be chosen on a diagram. Secondary information regarding flush volume was also collected and free-text responses encouraged. Results: There were 42 nurses employed in Dunedin NICU during this period, of whom 37 (88%) responded. For a 24-week gestation baby, 34 nurses (92%) would administer into the primary lumen (20ga), containing 10% dextrose (0.5 mL/hr), compared to 3 (8%) who would use the secondary lumen (23ga), containing parenteral nutrition fluid (2.1 mL/hr). For a 32-week gestation baby 35 nurses (95%) would administer through the slow-flowing primary lumen. If a peripheral intravenous line (PIV) was present this would be used preferentially by 35 nurses (95%) to reduce the risk of infection. Smaller flush volumes were documented following administration through the UVC compared with PIV (1.17–1.35 mL vs 2.4 mL at 24 weeks and 1.42–1.74 mL vs 3.2 mL at 32 weeks). Discussion: The variability in intravenous delivery route may be a significant contributor to variability in neonatal gentamicin pharmacokinetics.